A cyclic peptide significantly improves thyroid function, thyrotropin-receptor antibodies and orbital mucine /collagen content in a long-term Graves' disease mouse model. Issue 122 (August 2021) - Diana, Tanja; Ungerer, Martin; Wüster, Christian; Faßbender, Julia; Li, Zhongmin; Reimann, Andreas; Holthoff, Hans-Peter; Kanitz, Michael; Kahaly, George J.
Abstract: Background: BALB/c mice which received long-term immunizations of adenovirus (Ad) expressing thyrotropin receptor A-subunits (TSHR) developed stable Graves' disease (GD). TSHR-derived cyclic peptide 19 (P19) was identified as effective therapy in this model. Methods: In Ad-TSHR mice, we investigated shorter disease intervals up to 4 months for histological alterations of the orbits, fine tuning of anti -TSHR antibodies (Ab) and free thyroxine (fT4) hormone levels by using novel detection methods in an independent laboratory. Therapy (0.3 mg/kg P19 or vehicle) was given intravenously after the fourth Ad-TSHR immunization (week 11) and continued until week 19. Results: Thyrotropin binding inhibitory immunoglobulins (TBII, bridge immunoassay), blocking (TBAb) and stimulating (TSAb) TSHR-Ab (both cell-based bioassays) and serum levels of fT4 were significantly elevated at week 11 in Ad-TSHR-immunized mice versus none in control mice. For the first time, TSAb, TBAb, and thyroperoxidase-Ab were detected in 17 of 19, 12/19 and 6/19 Ad-TSHR immunized mice, respectively at week 21. Also, for the first time, this study showed that P19 treatment markedly reduced serum TBII (p < 0.0001), serum fT4 (p = 0.02), and acidic mucins and collagen content in the orbital tissue of Ad-TSHR-immunized mice. Conclusion: P19 significantly improved thyroid function, confirming previous results in an independent second laboratory. A relevant shift of anti -TSHR antibody subpopulations in response to P19 therapy may help explain its immunological effects. Moreover, P19 exerted a beneficial effect on mucine and collagen content of orbital tissue. Hence, P19 offers a potential novel therapeutic approach for GD and associated orbitopathy. Highlights: Long-term Graves' disease mouse model verified/expanded in second laboratory. Hyperthyroidism noted after four immunizations with thyrotropin receptor (TSHR). Enhanced orbital mucine/collagen deposition in animal orbital tissue. Peptide P19 reduced thyroid dysfunction, TSHR-Ab, orbital mucine/collagen content. Thyroperoxidase-Ab in TSHR-immunized mice versus none in control mice.